Islet Cell Associated Autoantibodies and C-Peptide Levels in Patients with Diabetes and Symptoms of Gastroparesis - Siraj, Elias S.; Homko, Carol; Wilson, Laura A.; May, Patrick; Rao, Ajay D.; Calles, Jorge; Farrugia, Gianrico; Hasler, William L.; Koch, Kenneth L.; Nguyen, Linda; Snape, William J.; Abell, Thomas L.; et al. (Frontiers in endocrinology (Lausanne), 2018)
Individuals with diabetes are at increased risk for complications, including gastroparesis. Type 1 diabetes mellitus (T1DM) is an autoimmune disorder resulting in decreased beta-cell function. Glutamic acid decarboxylase-65 antibody (GADA) is the most commonly used test to assess autoimmunity while C-peptide level is used to assess beta-cell function. Patients with type 2 diabetes mellitus (T2DM), who are GADA positive, are labeled latent autoimmune diabetes in adults (LADA). To characterize patients with T1 and T2DM who have symptoms of gastroparesis using GADA and C-peptide levels and to look for association with the presence of gastroparesis and its symptom severity. 113 T1DM and 90 T2DM patients with symptoms suggestive of gastroparesis were studied. Symptom severity was assessed using Gastroparesis Cardinal Symptom Index (GCSI). Serum samples were analyzed for GADA and C-peptide. Delayed gastric emptying was present in 91 (81%) of T1DM and 60 (67%) of T2DM patients ( = 0.04). GADA was present in 13% of T2DM subjects [10% in delayed gastric emptying and 20% in normal gastric emptying ( = 0.2)]. Gastric retention and GCSI scores were mostly similar in GADA positive and negative T2DM patients. GADA was present in 45% of T1DM subjects [46% in delayed gastric emptying and 41% in normal gastric emptying ( = 0.81)]. Low C-peptide levels were seen in 79% T1DM patients and 8% T2DM. All seven T2DM patients with low C-peptide were taking insulin compared to 52% of T2DM with normal C-peptide. GADA was present in 13% while low C-peptide was seen in 8% of our T2DM patients with symptoms of gastroparesis. Neither did correlate with degree of delayed gastric emptying or symptom severity. NCT01696747.